Design and Development of Healthcare System based on Internet of Things-Review - Gawande, GS; Thakare, SA; Wankhede, PR (International Journal of Computer Sciences and Engineering, 2025)
Healthcare systems have grown to be a crucial research area today. Chronic diseases and the cardiovascular diseases are the biggest challenge for India and these diseases are the main cause for the hospitalization of the elderly people. For this purpose, there is need to monitor some parameters of the patient continuously. This system is designed and developed for the remote patient monitoring in the healthcare field. It affords a useful tool where doctor can monitor the heart condition i.e. blood pressure and heart rate with posture and temperature of the patient continuously using web server. Once, the abnormality of the patient’s condition is observed by the doctor, he can give the appropriate decision in the form of prescription to the caretaker of the patient. The availability of this system can help the physician to cover the distance between himself and the patient which helps in early recovery of the patient.